Brassinosteroid Biosynthesis Is Modulated via a Transcription Factor Cascade of COG1, PIF4, and PIF5. Issue 2 (24th April 2017) - Wei, Zhuoyun; Yuan, Tong; Tarkowská, Danu¡e; Kim, Jeongsik; Nam, Hong Gil; Novák, Ondřej; He, Kai; Gou, Xiaoping; Li, Jia
Abstract : Transcriptional control of brassinosteroid biosynthesis genes engages a transcription factor cascade in Arabidopsis. Abstract: Brassinosteroids (BR s) are essential phytohormones regulating various developmental and physiological processes during normal growth and development. cog1-3D ( cogwheel1-3D ) was identified as an activation-tagged genetic modifier of bri1-5, an intermediate BR receptor mutant in Arabidopsis ( Arabidopsis thaliana ). COG1 encodes a Dof-type transcription factor found previously to act as a negative regulator of the phytochrome signaling pathway. cog1-3D single mutants show an elongated hypocotyl phenotype under light conditions. A loss-of-function mutant or inducible expression of a dominant negative form of COG1 in the wild type results in an opposite phenotype. A BR profile assay indicated that BR levels are elevated in cog1-3D seedlings. Quantitative reverse transcription-polymerase chain reaction analyses showed that several key BR biosynthetic genes are significantly up-regulated in cog1-3D compared with those of the wild type. Two basic helix-loop-helix transcription factors, PIF4 and PIF5, were found to be transcriptionally up-regulated in cog1-3D . Genetic analysis indicated that PIF4 and PIF5 were required for COG1 to promote BR biosynthesis and hypocotyl elongation. Chromatin immunoprecipitation and electrophoretic mobility shift assays indicated that COG1 binds to the promoter regions of PIF4 and PIF5, and PIF4 and PIF5 bind to the promoter regions of key BR biosynthetic genes, such as DWF4 and BR6ox2, to directly promote their expression. These results demonstrated that COG1 regulates BR biosynthesis via up-regulating the transcription of PIF4 and PIF5 .